SQL injection attacks and defense - Clarke, Justin (Syngress, 2009)
Winner of the Best Book Bejtlich Read in 2009 award!"SQL injection is probably the number one problem for any server-side application, and this book is unequaled in its coverage." Richard Bejtlich, http://taosecurity.blogspot.com/SQL injection represents one of the most dangerous and well-known, yet misunderstood, security vulnerabilities.